(untitled) (Homoeopathy for All, 2024)
Obsessive Compulsive Disorder is an anxiety disorder that affects 0.5 to 4% of the population in childhood and adolescence. It is characterized by persistent, unwanted obsessions and compulsions. Since the exact cause of OCD is still unknown, a few factors, including behavioral, cognitive, biochemical, genetic, and environmental ones, have been identified. The purpose of this article is to discuss how treating OCD with homeopathy can help an individual improve their way of life.